Investigating cyber-loafing in South African organisations: the role of theory of planned behaviour - Werner, Jenna (University of Cape Town, 2021)
Organisations are increasingly becoming aware of employees' internet use for nonwork- related activities, a phenomenon known as cyber-loafing. This poses a problem for organisations as both employee and organisational productivity are negatively impacted. Cyber-loafing is a fairly nascent concept within the Counterproductive Work Behaviour (CWB) literature, given the recent rise in technological advancements. Employees who engage in cyber-loafing divert their energy and attention away from work for prolonged periods of time, which is classified as a withdrawal behaviour under the CWB typology. The Theory of Planned Behaviour (TPB) has previously been shown to explain other CWBs, such as time theft and cyber-loafing. Due to the internet's ubiquitous nature in South African organisations and lack of research on cyber-loafing in South Africa, the objective of this study was to investigate cyber-loafing amongst administrative support staff in South African organisations using TPB. An explanatory cross-sectional descriptive research design was used. Data was collected using both online and hardcopy surveys yielding 92 participants from employees that provide administrative assistance in various organisations. In this sample, 89% of respondents were female and 11% were male, whilst 92% were employed full-time and 5% part-time. The results showed that only descriptive and prescriptive norms and attitude towards cyber-loafing predicted intention and cyber-loafing. Differing from previous research, intention mediated the relationship between attitude and cyber-loafing only. The results show that organisations could develop interventions targeted at descriptive and prescriptive norms to reduce cyber-loafing behaviour and by influencing attitudes around cyber-loafing, organisations could influence cyber-loafing intention and behaviour. Based on these results, suggestions for further research are proposed.